2010
DOI: 10.1111/j.1532-5415.2009.02648.x
|View full text |Cite
|
Sign up to set email alerts
|

Intensive Stepwise Method for Oral Intake Using a Combination of Transient Receptor Potential Stimulation and Olfactory Stimulation Inhibits the Incidence of Pneumonia in Dysphagic Older Adults

Abstract: herd effect of PCV7 would be similar in nonbacteremic cases and IPD, the results of the current study suggest a possible combined effect of PPV23 (direct) and PCV7 (indirect) against NBPCAP in older adults. Further studies are needed to elucidate the direct and indirect benefits of pneumococcal vaccinations against NBPCAP in older adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 9 publications
(11 reference statements)
0
33
0
Order By: Relevance
“…In our studies, we found significant therapeutic effects at 150 μM for piperine (and maximal therapeutic effect at 1 mM) and at 150 μM for natural capsaicinoids . In addition, capsaicin boluses also improved the efficacy of swallow by reducing the prevalence of oropharyngeal residue via increasing the tongue propulsion force, and the midterm use of these strategies seem to improve brain plasticity . All of these studies included groups of patients with poststroke OD, where these agonists showed significant effects on VFS signs of swallow response.…”
Section: Advances In Treatmentmentioning
confidence: 58%
“…In our studies, we found significant therapeutic effects at 150 μM for piperine (and maximal therapeutic effect at 1 mM) and at 150 μM for natural capsaicinoids . In addition, capsaicin boluses also improved the efficacy of swallow by reducing the prevalence of oropharyngeal residue via increasing the tongue propulsion force, and the midterm use of these strategies seem to improve brain plasticity . All of these studies included groups of patients with poststroke OD, where these agonists showed significant effects on VFS signs of swallow response.…”
Section: Advances In Treatmentmentioning
confidence: 58%
“…3). This sheet easily and stably provides olfactory stimulation using the aroma component of black pepper oil by changing the aroma patch sheet daily (31). It is almost equally as effective as direct black pepper oil stimulation.…”
Section: Swallowing Improvement By Olfactory Stimulation Using Black mentioning
confidence: 94%
“…The most important and challenging step in aspiration pneumonia treatment is restarting eating after recovery using antibiotic treatment. We developed a protocol to restart eating in patients with feeding and swallowing disorders by a combination of aromatherapy, spices, oral care, and swallowing rehabilitation (31). Implementation of this protocol helped avoid re-aspiration as well as gastrostomy in many elderly people.…”
Section: Future Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Using this protocol, the incidence of pneumonia and the number of febrile days for 1 month from the start of oral intake were signiˆcantly reduced. 30) Implementation of this protocol would help avoid reaspiration in many elderly people with aspiration pneumonia. In addition, this protocol is also applicable to feeding training and rehabilitation of all feeding and swallowing disorders.…”
Section: Discussionmentioning
confidence: 99%